Providers’ Competencies and Management Practices for Traditional Palliative Cancer Care Service Delivery in Kenya - Solomon K Cheboi; Wanjiru S Ng’ang’a; Philamon Nyamanga; Stanley Kibet (Health Services Insights, 2023)
Background: Many people in developing countries are struggling with chronic diseases yet traditional health services remain under-utilized in the quest for universal health care. Thousands patronize these outlets for care yet little is known about provider’s competence and how these competencies inform palliative care decisions and practices. The study documented traditional health practitioners (THPs) competencies and practices for traditional palliative cancer care service delivery in Kenya. Methods: This study utilized mixed-methods design and was undertaken in major towns across Kenya. A total of 201 Traditional health practitioners were purposely sampled, and interviewed. Five in-depth interviews and 6 focus group discussions were conducted. Quantitative data were analyzed using SPSSv22 while thematic and discourse analysis was carried out for qualitative data. Results: Majority (92.7%) of the THPs provided general traditional health services. Nearly half of the respondents (47.7%, n = 92) stated that they had received their knowledge and abilities through divine gifting, 71 (36.8%) lineage, 61 (31.6%) apprenticeship, and 39 (20.2%) formal study. Palliative care was determined by patient state and followed consultation with caregivers for 165 (85.5%) of respondents. For 160 respondents (83%), management practices involved a mix of patient examination, conventional medical tests, herbal medicine administration, follow-up or referral. Positive feedback consisted of symptom reduction and function recovery. Conclusion: Core competencies identified include: knowledge acquisition and specialization, assessment, diagnosis and disclosure, decision making, treatment, follow-up, and referral. Traditional palliative care providers share common health-related beliefs, practices and abilities that influence how they approach and make decisions regarding the health management of their patients, despite marked ethnic diversity. The shared pathways offer a chance to develop a cogent traditional palliative care service delivery model and health policy framework to promote its integration within the health workforce. The leading unmet requirements are knowledge of intellectual property rights, disclosure frameworks, and ethical regulation principles.